O Catador de Material Reciclável (Re)Tratado sob a Ótica da Análise Coletiva do Trabalho - Barella, Francieli Maria (2017)
The main of the study was to understand the profession of Recyclabe Material Colectors in the light of the Colletive Analysis of Work (ACT) that work in AGECO (Association of Ecological Agents of the Recyclable Materials of Prudentópolis), in the southern center of the state of Paraná, Brazil. The theoretical background was focused on the significance of the photos taken by the workers themselves made with the pinhole camera manufactured by them, with the following ACT question: "What do you do at work?. From the photos, a conversation with the workers and a field diary, there was a feeling of neglect and abandonment that they felt in relation to their profession, both the public authorities and the population, one for not maintaining the physical environment of their work and others for the incorrect and meager separation of the waste that arrive to AGECO. Thus, it is concluded that the development of this community runs through a set of internal and external factors to these workers and that even being seen as a marginalized profession we can extract art and feelings, as well as the analogical images made with the pinhole cameras, where at the first contact we have the negative, with images that are not very clear and dark, but when passing through the processes of revelation, where an analogy can be made to the process of knowledge and understanding of the work of these people, the images become much sharper and clear, a negative and positive view at this category of work.